1991
DOI: 10.1111/j.1365-2621.1991.tb05390.x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Effects of pH and NaCl on Heat Resistance of Bacterial Spores

Abstract: Spores of PA3679 (C. sporogenes) and Clostridiwn botulinum 213B were less heat resistant when heated in a menstruum of decreasing pH. The D value of the spore population decreased by 50% when heated in pH 5.0 buffer compared to pH 7.0 buffer. Addition of NaCl to the recovery medium reduced the number of colony forming units in a population of heated spores. Presence of NaCl at 2.0% in the recovery medium decreased the spore D-value by 20-40% irrespective of pH of the heating menstruum. Combined effects of pH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Due to the shift of dissociation equilibria during heating and/or compression the results of inactivation experiments are prone to error if not designed correctly. Different authors showed that there is a strong pH dependence of spore inactivation during thermal treatment (Alderton, Ito, & Chen, 1976;Cameron, Leonard, & Barrett, 1980;Hutton, Koskinen, & Hanlin, 1991;Loewick & Anema, 1972;Sognefest, Hays, Wheaton, & Benjamin, 1948). The same dependence was observed during highpressure inactivation (Ardia, 2004;Wuytack, 1999;Wuytack & Michiels, 2001).…”
Section: Introductionmentioning
confidence: 71%
“…Due to the shift of dissociation equilibria during heating and/or compression the results of inactivation experiments are prone to error if not designed correctly. Different authors showed that there is a strong pH dependence of spore inactivation during thermal treatment (Alderton, Ito, & Chen, 1976;Cameron, Leonard, & Barrett, 1980;Hutton, Koskinen, & Hanlin, 1991;Loewick & Anema, 1972;Sognefest, Hays, Wheaton, & Benjamin, 1948). The same dependence was observed during highpressure inactivation (Ardia, 2004;Wuytack, 1999;Wuytack & Michiels, 2001).…”
Section: Introductionmentioning
confidence: 71%
“…In view of the dissociation equilibrium shift during heating, a biased error in the results of inactivation experiments occurs, which leads to incomparable results if they are not designed correctly. Several authors have shown that the thermal inactivation of bacterial spores, [8][9][10][11][12] vegetative microorganisms, [13] or protein and enzyme denaturation [14][15][16] strongly depends on the pH of the suspending media. According to Goldberg, [17] the known temperature dependence of the acid dissociation constant K a (T) for different buffer systems could be interpolated up to 60 • C.…”
Section: Introductionmentioning
confidence: 99%
“…However, with several foods, it is not necessary to submit them to severe processes, because for a variety of reasons related to the nature of the food and the presence of some approved food additives, the surviving spores may not be able to germinate and grow in the processed foods; recommended sterilization procedures should therefore take account of this. Extensive research has been conducted into the role of pH (Cook and Brown 1965;Cook and Gilbert 1968;Mallidis and Scholefield 1986;González et al 1996;López et al 1997), sodium chloride (Labbe 1979;Feeherry et al 1987;Hutton et al 1991;González et al 1997;López et al 1997) and nitrite content (Ingram and Roberts 1971;Chumney and Adams 1980) in controlling recovery of spore-forming bacteria. However, literature data on the influence of some food additives in the recovery medium on the heat resistance of spores are scarce .…”
Section: Introductionmentioning
confidence: 99%